2018
DOI: 10.3390/su10082791
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cooperation among Stakeholders in PPP Mega-Infrastructure Projects: A China Study

Abstract: Despite the consensus that enhanced cooperation among stakeholders is critical to the successful delivery of public-private partnership (PPP) mega-infrastructure projects, there has been a limited utilization of the quantitative approach to explore the cooperation mechanism. Drawing on research and the actual practice of PPP projects in China, a quantitative mathematical model using evolutionary game theory is constructed to explore the internal cooperation mechanism. Numerical simulation is implemented to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…, and D 7 (0, 0, 1). The stability of the local equilibrium point can be obtained by the analysis of the system's Jacobian if a system of differential equations describing population dynamics is known [21], which is…”
Section: Game Players Parameters Meaningsmentioning
confidence: 99%
See 1 more Smart Citation
“…, and D 7 (0, 0, 1). The stability of the local equilibrium point can be obtained by the analysis of the system's Jacobian if a system of differential equations describing population dynamics is known [21], which is…”
Section: Game Players Parameters Meaningsmentioning
confidence: 99%
“…The final operation of PPP project depended on the cost and benefit of all parties [20]. Li et al found that the supervision strategy was not chosen when the supervision cost of government supervision department was greater than the supervision benefit; it could make private sector consciously provide the high-quality public products/services with the improvement of public participation level [21].…”
Section: Introductionmentioning
confidence: 99%
“…The cooperation and proper management among different stakeholders are crucial for the success of the PPP project (L. Li, Z. F. Li, Jiang, Wu, & Cheng, 2018;Amadi & Carrillo, 2018). Similarly, a successful PPP project should satisfy the requirements of the stakeholders (Liang & Jia, 2018).…”
Section: Assessment Index Systemmentioning
confidence: 99%
“…Guo, et al [58] conducted research on the quality supervision activities among construction stakeholders by using evolutionary game theory. Li [59] constructed a mathematical model to enhance cooperation among stakeholders in PPP mega-infrastructure projects. Sun [60] constructed a model for construction employers, workers and government to analyze their attitudes towards vocational skills trainings.…”
Section: Use Of Evolutionary Game Theory In Construction Industrymentioning
confidence: 99%